Moving the dial on prenatal stress mechanisms of neurodevelopmental vulnerability to mental health problems: A personalized prevention proof of concept. Issue 4 (22nd November 2020) - Wakschlag, Lauren S.; Tandon, Darius; Krogh‐Jespersen, Sheila; Petitclerc, Amelie; Nielsen, Ashley; Ghaffari, Rhoozbeh; Mithal, Leena; Bass, Michael; Ward, Erin; Berken, Jonathan; Fareedi, Elveena; Cummings, Peter; et al.
Abstract: Prenatal stress exposure increases vulnerability to virtually all forms of psychopathology. Based on this robust evidence base, we propose a "Mental Health, Earlier" paradigm shift for prenatal stress research, which moves from the documentation of stress‐related outcomes to their prevention, with a focus on infant neurodevelopmental indicators of vulnerability to subsequent mental health problems. Achieving this requires an expansive team science approach. As an exemplar, we introduce the Promoting Healthy Brain Project (PHBP), a randomized trial testing the impact of the Wellness‐4‐2 personalized prenatal stress‐reduction intervention on stress‐related alterations in infant neurodevelopmental trajectories in the first year of life. Wellness‐4‐2 utilizes bio‐integrated stress monitoring for just‐in‐time adaptive intervention. We highlight unique challenges and opportunities this novel team science approach presents in synergizing expertise across predictive analytics, bioengineering, health information technology, prevention science, maternal – fetal medicine, neonatology, pediatrics, and neurodevelopmental science. We discuss how innovations across many areas of study facilitate this personalized preventive approach, using developmentally sensitive brain and behavioral methods to investigate whether altering children's adverse gestational exposures, i.e., maternal stress in the womb, can improve their mental health outlooks. In so doing, we seek to propel developmental SEED research towards preventive applications with the potential to reduce the pernicious effect of prenatal stress on neurodevelopment, mental health, and wellbeing.